Integration of green supply chain management practices in construction supply chain of CPEC. Issue 1 (13th January 2020) - Ali, Yousaf; Saad, Talal Bin; Sabir, Muhammad; Muhammad, Noor; Salman, Aneel; Zeb, Khaqan
Abstract : Purpose: China Pakistan Economic Corridor (CPEC) projects are widely spread throughout Pakistan with the potential to have a massive impact on Pakistan's economic future. CPEC projects have, therefore, made it imperative that green practices are adapted to provide sustainability to the CPEC projects. The adoption of green supply chain management (GSCM) framework will significantly increase the value attained from CPEC projects through the increased benefits to the socio-cultural and economic conditions of Pakistan without causing harm to the environment. The purpose of this paper is to identify and rank the GSCM practices for implementation in the construction industry of Pakistan according to expert opinion. Design/methodology/approach: This study targets the experts who are employed as supply chain managers in the different construction industries of Pakistan. The opinions of these experts have been extracted through an online questionnaire that was based on six alternatives along with four criteria. The tool of multi-criteria decision making (MCDM) that is a Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) has been used to analyze the results. Findings: Six alternatives that have been used for this study are green design, green procurement, green production, green warehousing, green transportation and green recycling. The top-ranked alternative as a practice for GSCM is green warehousing followed by green production. The lowest ranked alternative in this study is green recycling. The alternatives have been ranked on the basis of "cc" values derived through TOPSIS. Practical implications: As the advancement in the construction industry will definitely going to impact the environmental sustainability of the country, the results derived through this research will assist the managers of the construction industry of Pakistan to adopt best practices among green supply chain in order to lower their impact. Originality/value: Framework using TOPSIS in order to find the best GSCM practice in Pakistan has not been reported before this study.